Four children and It - Wilson, Jacqueline (Puffin London, 2013)
This is a funny, moving and heartwarming story of four children who discover a way to make wishes come true. Echoing the classic E. Nesbit novel, 'Five Children and It', this new story is a great read not just for those familiar with the original book but for any of Wilson's millions of fans